The Omnibus Law Concept in the Job Creation Law and the Legal Consequences for Limited Liability Companies - Dewinagara, Trisya Benazir; Handayani, I Gusti Ayu Ketut Rachmi; Purwadi, Hari (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The concept of Omnibus Law is intended as a means to resolve conflicting norms between laws and regulations so that inconsistencies do not occur.Purposes of the Research: The study aimed to evaluate the concept of the Omnibus Law against the Job Creation Law (Undang-Undang Cipta Kerja) with a more specific focus on Limited Liability Company Regulations.Methods of the Research: Normative legal research (doctrinal study) on policies with a Conceptual Approached and Legislation (normative-juridical).Results of the Research: That many sectors of law grouped into the Omnibus Law, which was prone to causing inconsistencies, Lack of clarity in rules resulted in a lack of legal certainty, especially for Limited Liability Companies; the emergence of inconsistencies in the Job Creation Law against the UUPT due to a new concept regarding SMEs Limited Liability Companies or individual Limited Liability Companies which has legal consequences, the emergence of responsibility for piercing the corporate veil because there is only one shareholder; the absence of the role of a notary and an authentic deed of establishment; changed and dissolution of the RUPS SMEs Limited Liability Companies through an electronic statement letter will cause a lack of legal validity of the Limited Liability Company; absence of a minimum capital requirement could lead to vulnerabilities in providing third party payment guarantees; moreover, setting limits for the establishment of the founders of the SMEs company may only be once a year, creating the risk of branching creditors; and provide an opportunity of creating Limited Liability Companies to seek profits every year, based on a limited liability concept.